Roman StandardsTheir Types, Symbolic Significance, and Military Role (Damascus University Journal of Historical Studies, 2025)
This research examines the central role of military standards in the Roman army, where they were not merely distinguishing marks for units but also symbols of the Empire's power and prestige. They played an active role in fostering patriotism and discipline among soldiers. Special emphasis is placed on the Aquila as the primary symbol of the imperial armies, along with an analysis of the specialized roles of standard bearers, such as the Aquilifer and Vexillarius, who played a crucial role in boosting soldiers' morale and coordinating military actions during critical moments in battles.The analysis includes the evolution of the standards' design over the ages, reflecting the cultural and political changes experienced by the Empire. Standards were not merely practical tools but bore sacred symbols, making them integral to religious and formal rituals, as seen in wall paintings like those discovered in Dura-Europos and in coins bearing standard symbols.This research draws on historical sources and archaeological evidence to illustrate how standards became symbols of the soldiers' devotion and deep loyalty to the empire. Standards, in their various forms, not only reinforced Roman identity but also served as a means to legitimize the emperor's rule and express the military might of Rome.
Keywords: Roman army; Military standards; Symbols; Religious symbolism; Vexillarius; Aquilifer; Aquila